The Role of Nursing in Reducing Laboratory Errors through Specimen Management: A Narrative Review - Alharbi, Mizinha Aied; Amani Nadheem Aldhefeeri; Nouf Turki Lafi Alhomaidani; Amani Obaid Mathan Alruwaili; Mona Atua Soud Alshammri; Dlaiel Thany ALdhafeeri; Ghazal Abdulrahman Surayyi Alotaibi; Fetim Sultan Al Harbi; Fatimah Eid Alshammri; Hana Fehid Sagheer Aldhafeeri; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Laboratory diagnostics underpin up to 70% of clinical decisions, yet 40-70% of laboratory errors occur in the pre-analytical phase—a process largely controlled by nursing during specimen collection and handling. Preventable errors in identification, technique, and transport persist, causing patient harm and systemic inefficiency. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review synthesizes evidence on nursing’s pivotal role in specimen management, analyzes error root causes, and evaluates the effectiveness of nursing-led interventions aimed at improving laboratory safety and specimen quality. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A systematic literature search (2010-2025) was performed across PubMed, CINAHL, Scopus, and Web of Science using relevant keywords. The analysis focused on error epidemiology, causative factors, and intervention outcomes related to education, technology, and system redesign. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Nursing practice is the decisive factor for pre-analytical quality. Primary errors stem from misidentification, incorrect tube use, poor technique causing hemolysis, and improper handling. Effective, multimodal interventions include sustained competency-based education, barcode patient identification systems, standardized kits, dedicated phlebotomy teams, and closed-loop quality feedback, collectively reducing errors by 50-80%. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Nurses are fundamental guardians of diagnostic integrity. Sustainable error reduction necessitates a systemic, non-punitive strategy integrating robust education, smart technology, standardized workflows, and a supportive culture. Empowering nursing in this domain is a critical lever for enhancing patient safety, diagnostic accuracy, and healthcare value.